Pengembangan Video Edukatif Volume Bangun Ruang Berbasis Etnomatematika Makanan Tradisonal Via Youtube - Afifudin Lisgianto; Huri Suhendri (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
The purpose of this research is to produce an educative video of volume building based on the ethnomathematics of traditional food through Youtube. This study uses the Hannafin and Peck development model which consists of 3 stages, namely the needs analysis stage (Analyze), the design stage (Design), the development and implementation stages (Development & Implementation). Collecting data in this study using interviews and questionnaires. The instruments that accompany this research are a material expert and media expert validation questionnaire sheet, as well as a small group trial questionnaire. The results of the validation in the study showed that the educational video developed had met the eligibility criteria for the material expert test with a proportion of 78.9%, met the criteria very feasible for the media expert test with a proportion of 82.4%, met the eligibility criteria for a small group trial with a percentage of 77 ,5%. Based on these results, the ethnomathematics-based educational video developed is feasible to be used as a medium for learning mathematics in SMK.Keywords: Educational video, Spatial Building Volume, Ethnomathematics, Youtube